Women living with AIDS in rural Southern India: Perspectives on mental health and lay health care worker support. Issue 2 (3rd April 2017) - Srivastava, Neha; Nyamathi, Adeline M.; Sinha, Sanjeev; Carpenter, Catherine; Satyanarayana, Veena; Ramakrishnan, Padma; Ekstrand, Maria
ABSTRACT: In this study, focus groups were conducted with 16 rural women living with AIDS (WLA) from Andhra Pradesh, India, who had previously participated in a clinical trial wherein 68 WLA were randomized into either an Accredited Social Health Activists (ASHA)-Life (AL) intervention or a usual care program. Findings are discussed in terms of (a) mental health issues, (b) perceived stressors, (c) individual resources for coping with mental health issues, and (d) role of ASHA support in coping with mental health issues. These findings highlight the salience of mental health issues in the lives of WLA and the role played by ASHA in addressing some of these issues. The discussion section makes a case for increased emphasis on mental health care in future community-based interventions for this population.